The Effectiveness of Problem-Based Learning on Advanced Reading Comprehension Skill in Online Arabic Language Teaching - Hasyim, Mohamad Yusuf Ahmad (IAIN Salatiga, 2021)
Reading proficiency is considered as one of the language skills that must be mastered by prospective Arabic educators or practitioners. Besides, in the era of industry 4.0, students not only require core competencies from the field of study they are studying but also have a lifelong character of a learner. The conditions found in the field, as well as in previous studies, showed that learning in higher education currently tends to be centred on lecturers rather than on the students. This study aims to examine the effectiveness of the implementation of a student-centred learning method in the form of a problem-based learning method with seven-jumps (seven-steps) approach in increasing the reading proficiency in Arabic. The subjects of this research were 50 people of Muthala’ah Mukatsafah class, and the test and non-test were employed as instruments. The reading proficiency test prepared by the researcher was used to figure out the subjects’ reading ability. Meanwhile, the subjects’ characters or soft skills were measured through a non-test instrument in the form of a questionnaire. The design applied in this study was a group design (one group pretest-posttest design). The data analysis was performed through a significance test before and after treatment. The results show that there are differences in the subjects’ advanced reading proficiency level as well as an increase in empathy soft skill before and after the implementation of the learning method.